Peran Religiusitas Sebagai Variabel Moderating Pengetahuan, Persepsi Produk Bank Syariah dan Literasi Keuangan Tehadap Minat Investasi Syariah - Dwi Nur Agustin; Luqman Hakim (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
The progressive development of sharia banking in Indonesia is quite significant, so many use sharia-based products, one of which is sharia investment. Apart from Islamic law, several factors influence students to invest in sharia: knowledge, perceptions of sharia banking products, and financial literacy. This study was conducted to determine the effect of knowledge, perceptions of sharia bank products, and financial literacy with religiosity as a moderating variable on sharia investment interest. This research utilizes quantitative research methods with purposive sampling as a sampling technique with 100 students as respondents. Google form is used as a research instrument to obtain the accuracy of the results. Then the data were analyzed using Structural Equation Modeling. From the results of this research analysis, knowledge can influence interest in sharia's investment. However, it is less significant on the variable interest in sharia investment. At the same time, the perceptions of Sharia bank products and financial literacy have a positive and significant effect on interest in Sharia investment. Then religiosity can moderate knowledge, perceptions of sharia bank products, and financial literacy on sharia investment interest.